Letterbox Companies and the Corporate Mobility Regime in the EU After Directive 2019/2121 - Ariel Mucha (Review of European and Comparative Law)
This paper analyses the solutions aimed at fighting letterbox companies introduced alongside certain enabling rules on cross-border corporate restructuring transactions, namely conversions, mergers and divisions, into the Company Law Directive (2017/1132). The new law introduces an anti-abuse clause, which is embedded into the certification procedure of each cross-border restructuring. The results of the analysis suggest that the new anti-abuse tool lacks an accurate indication of what type of practices it is supposed to curb. Additionally, the law allows public authorities to view letterbox companies as systemic threats to the values of the single market without providing compelling reasons for such an assessment.